KEEFEKTIFAN PENYULUHAN PERTANIAN DALAM MENINGKATKAN PRODUKSI TANAMAN JAGUNG DI KABUPATEN LANGKAT PROVINSI SUMATERA UTARA - Mukhlis Yahya; Herawaty; Misiyem; Eka Widya Lestary (Politeknik Pembangunan Pertanian Medan, 2020)
The study was conducted in Langkat Regency, North Sumatra Province with the aim of: 1) To find out the effectiveness of agricultural extension in increasing corn production in Langkat District. 2) To find out the factors that influence the effectiveness of agricultural extension in increasing corn production in Langkat Regency. The research method used was a survey, the data analysis method used is to calculate the percentage score acquision and multiple linear regression analysis. The results showed that the level of effectiveness of agricultural extension in increasing corn production in Langkat Regency was classified as very effective at 82.97%. Based on testsing conducted only one factor that influenced the effectiveness of agricultural extension in increasing corn production in Langkat District was the media extension factor (X3) by 68.4% while the rest were influenced by other factor not examined in this research.